2007
DOI: 10.1016/j.otohns.2007.06.737
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic and endoscopic analysis of supraorbital ethmoid cells

Abstract: A thorough knowledge of endoscopic anatomy and CT of the frontal recess and various fronto-ethmoid cells were required for safe dissection of the SOEC and frontal ostium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 21 publications
0
36
1
2
Order By: Relevance
“…11,14 The posterior groups of the cells in the ethmoid bulla are supraorbital ethmoid cells, suprabullar cells, and frontal bullar cells. They do not disturb the approach via the route anterior to the ethmoid bulla.…”
Section: Discussionmentioning
confidence: 99%
“…11,14 The posterior groups of the cells in the ethmoid bulla are supraorbital ethmoid cells, suprabullar cells, and frontal bullar cells. They do not disturb the approach via the route anterior to the ethmoid bulla.…”
Section: Discussionmentioning
confidence: 99%
“…It might be single or multiple and might open into the lateral aspect of the frontal recess 2. On coronal CT images, SOECs are found lateral to the frontal sinus, whereas the FBCs are medial to it 8. In a study of SOECs in 57 Korean and 41 white subjects, Cho et al7 found that SOECs were more frequent in the white population (64.6%) than in the Korean population (2.6%).…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography (CT) is an invaluable adjunct to diagnostic nasal endoscopy in identifying various causes of frontal recess obstruction. Many studies of frontal recess pneumatization patterns assessed by CT have been published, but only a few of them have focused on Asian adult populations 7–9. Anatomically, SBCs and FBCs occur posteriorly in the frontal recess along the skull base, and ANCs and FCs occur anteriorly in the frontal recess 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These cells drain into the lateral aspect of the FR [57]. Because of the close relation between the SOEC and anterior ethmoidal artery, enlarging the SOEC could risk damage to the artery [59]. …”
Section: Supraorbital Ethmoid Cellmentioning
confidence: 99%